Искра жизни: [роман / перевод с немецкого В. Котелкина] - Ремарк Эрих Мария (1992)
Экземпляры: ф.2 (1993) / Инвентарный номер: 36565 / Цена: / Сис.шифр: 84(4Гем)-4 / Авт.знак: Р 37 / ГРНТИ: 17.82.31 / ББК: 84(4Гем)-44